An improved DV-Hop algorithm based on distance optimisation for WSNs. (29th July 2019) - Tang, Fei; Chen, Sanfeng; Lin, Guangming
To improve the localisation accuracy for unknown nodes within a one-hop distance of an anchor node, this paper analysis the main reason that results in localisation error of DDV-Hop localisation algorithm, which is the estimation of the number of hops between nodes. The localisation algorithm based on distance optimisation is proposed. Jaccard coefficient is conducive to reduce the estimation error on the number of hops to an unknown node at a one-hop distance, and the difference error coefficient of the DDV-Hop algorithm is used to reduce the error accumulated when calculating the average hop distance to correct the average hop distance between nodes. A credibility factor is introduced to select the anchor node for localisation, which can calculate the locations of nodes. The node with the highest localisation accuracy is used as a new anchor node. Simulation results show that under the same conditions, the improved algorithm has a higher localisation accuracy than both the DDV-Hop algorithm and DV-Hop algorithm. The algorithm proposed in this paper is of great significance to the localisation performance of wireless sensor networks.